ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR DAGING SAPI DI INDONESIA - Asima Ronitua Samosir Pakpahan (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2012)
Increase of population and living standard’s improvements will increase the consumption, including consumption of beef. Increasing beef consumption is followed by increasing productionof beef, therefore Indonesia has to import beef from other country. Imports of beef which annually increases give an impact on economic of Indonesia. This riset aims to analyze the factors that affect the increase of beef’s import except poduction and consumption of beef in Indonesia. Variables that used are price of imported beef, price of domestic beef, exchange rate, Gross Domestic Product and d97 (dummy variable). Analysis method of econometrics in this riset is error correction model (ECM). The research showed that: (1) data has been stationed in first difference, (2) data has been cointegratedt means there are correlation in the long term, (3) coefficient of ECT is 0,9134 and significant α =5% menas model that used are valid. The conclusion of research are (1) variables that used are significantly in the short term except price of domestic beef. (2) in the long term the variables have an effect on beef’s import significantly.